2017
DOI: 10.1186/s13075-017-1401-2
|View full text |Cite
|
Sign up to set email alerts
|

High titers of both rheumatoid factor and anti-CCP antibodies at baseline in patients with rheumatoid arthritis are associated with increased circulating baseline TNF level, low drug levels, and reduced clinical responses: a post hoc analysis of the RISING study

Abstract: BackgroundAlthough both rheumatoid factor (RF) and anticyclic citrullinated peptide antibodies (anti-CCP) are useful for diagnosing rheumatoid arthritis (RA), the impact of these autoantibodies on the efficacy of tumor necrosis factor (TNF) inhibitors has been controversial. The aim of this post hoc analysis of a randomized double-blind study (the RISING study) was to investigate the influences of RF and anti-CCP on the clinical response to infliximab in patients with RA.MethodsMethotrexate-refractory patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 42 publications
3
41
1
1
Order By: Relevance
“…Many groups have investigated rheumatoid factor (RF) and anti-citrullinated peptide antibody (ACPA) positivity to predict response to therapy of all biologics. The reports for anti-TNF therapy are either conflicting [22][23][24]28,29], or did not find a correlation [25,26]. A meta-analysis of 5561 patients also did not find an association between ACPA/RF status and anti-TNF response [27].…”
Section: Anti-citrullinated Peptide Antibodies and Rheumatoid Factormentioning
confidence: 99%
“…Many groups have investigated rheumatoid factor (RF) and anti-citrullinated peptide antibody (ACPA) positivity to predict response to therapy of all biologics. The reports for anti-TNF therapy are either conflicting [22][23][24]28,29], or did not find a correlation [25,26]. A meta-analysis of 5561 patients also did not find an association between ACPA/RF status and anti-TNF response [27].…”
Section: Anti-citrullinated Peptide Antibodies and Rheumatoid Factormentioning
confidence: 99%
“…In two previous studies on established RA, there was no significant relationship between RF positivity and ADAs to different biological agents, but the study populations included varied widely (4,13). Meanwhile, Takeuchi et al found in established RA an association between low autoantibody titres at baseline (RF and anti-CCP) and high levels of sIFX at follow-up (14). Although RF may interfere with standard cross-linking ELISA, our assay is an inhibition assay and control sera with high-titre RF do not give false-positive results.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, a major role for CD4 + CD28 + in SF of non‐RA patients, counterposed to the major role of CD8 + CD28null in SF of seronegative RA patients, may account for the good outcomes observed following treatment with the CD28/B7 modulator abatacept in PsA and even in gout patients, but not in seronegative RA . Moreover, while high titers of autoantibodies would predict a more aggressive disease in seropositive patients , measuring ZETA expression in SF T cells may be particularly useful for predicting arthritis severity in seronegative patients.…”
Section: Discussionmentioning
confidence: 99%